Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

Help solving nonlinear differential equation?

I need help solving the differential equation dy/dt=1/(t+y) given y(-1)=0

thanks!

2 Answers

Relevance
  • kb
    Lv 7
    1 decade ago
    Favorite Answer

    Invert both sides:

    dt/dy = t + y

    ==> dt/dy - t = y.

    This is linear in t, with integrating factor e^(-∫ 1 dy) = e^(-y):

    e^(-y) dt/dy - e^(-y) t = ye^(-y)

    ==> (d/dt) [-e^(-y) t] = ye^(-y)

    Integrate both sides:

    -e^(-y) t = -ye^(-y) - e^(-y) + C

    ==> t = -y - 1 + Ce^y

    Find C via (t, y) = (-1, 0):

    -1 = -0 - 1 + Ce^0

    ==> C = 0.

    Hence, the desired solution is t = -y - 1.

    ==> y = -t - 1.

    I hope this helps!

  • 1 decade ago

    Use an integrating factor to find the equation for the general solution:

    dy / dt = 1 / (t + y)

    dt / dy = t + y

    dt / dy - t = y

    dt / dy + P(y)t = f(y)

    P(y) = -1

    f(y) = y

    I(y) = e ^ ∫ P(y) dy

    I(y) = e ^ ∫ -1 dy

    I(y) = e ^ (-y)

    I(y)t = ∫ I(y)f(y) dy

    te ^ (-y) = ∫ ye ^ (-y) dy

    Integrate this function on the right side by parts:

    ∫ ye ^ (-y) dy

    Let f'(y) = e ^ (-y)

    f(y) = -e ^ (-y)

    Let g(y) = y

    g'(y) = 1

    ∫ f'(y)g(y) dy = f(y)g(y) - ∫ f(y)g'(y) dy

    ∫ ye ^ (-y) dy = -ye ^ (-y) + ∫ e ^ (-y) dy

    ∫ ye ^ (-y) dy = -ye ^ (-y) - e ^ (-y) + C

    ∫ ye ^ (-y) dy = -(y + 1)e ^ (-y) + C

    ∫ ye ^ (-y) dy = -(y + 1) / e ^ y + C

    Now plug this integral into the equation to get the general solution:

    te ^ (-y) = ∫ ye ^ (-y) dy

    te ^ (-y) = -(y + 1) / e ^ y + C

    t = -(y + 1) + Ce ^ y

    t = Ce ^ y - y - 1

    Finally solve for the constant to find the particular solution:

    When t = -1, y = 0

    -1 = C - 1

    C = 0

    t = -y - 1

    y = -t - 1

Still have questions? Get your answers by asking now.